Neglected children: Whose responsibility? Politics of protection of neglected children in Aceh Province Indonesia - Vellayati Hajad; Cut Irna Liyana; Ikhsan Ikhsan; Fernanda Putra Adela (Masyarakat, Kebudayaan dan Politik, 2023)
The Indonesian government defines neglected children as anyone under the age of eighteen who has not had their basic needs met. According to Article 34 of the 1945 Law, neglected children must be protected and become the responsibility of the state. However, in reality, neglected children are not fully protected. The purpose of this study is to learn about the policies in Aceh Province that protect neglected children. The qualitative research method was used, with a phenomenological approach. Data were gathered through interviews with informants, and from documents. After that, the data were analyzed using interpretive phenomenological analysis. The results of the study indicate that the problem of neglected children in Aceh occurs because the structure of the Acehnese society is improving after the long conflict and the tsunami disaster that resulted in community poverty. This study concludes that there are obstacles in the protection process related to: (1) The definition of neglected children so far is still one way (up-down); (2) Data collection is still hampered because many children in Aceh lack birth certificates, limiting their access to state services and protection.